Digital Transformations in Nordic Higher Education - Pinheiro, Rómulo; Edelhard Tømte, Cathrine; Barman, Linda; Degn, Lise; Geschwind, Lars (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book expands the scholarly and policy debates surrounding digital transformation in higher education. The authors adopt a pluralistic conceptual framework which uncovers three analytical elements - contexts, mediations, and type of effects - for unpacking empirical manifestations. The publicly funded higher education systems in Nordic countries provide solid empirical insights into how digital transformations have gained ground before and during the COVID-19 pandemic, and chapter contributions demonstrate how international digitalisation trends (such as in the global EdTech industry) impact on the core activities of higher education institutions (HEIs). The findings underscore the importance of assessments that consider multiple sub-systems within HEIs, as well as the complex relationships between them. By unpacking Nordic dynamics in the light of global processes and developments, the approach adopted and the results generated are of relevance to a much broader, global audience of students and researchers in higher education. Rómulo Pinheiro is Professor of Public Policy and Administration and Deputy Head in the Department of Political Science and Management at the University of Agder, Norway. Cathrine Edelhard Tømte is Professor in the Department of Information Systems and Deputy Director of the Center for Digital Transformation (CeDiT) at University of Agder, and Professor in the Center for the Science of Learning and Technology (SLATE), University of Bergen, Norway. Linda Barman is a lecturer at the Department of Learning in Engineering Sciences, KTH Royal Institute of Technology, Sweden. Lise Degn is Associate Professor in the Department of Political Science, Danish Centre for Studies in Research and Research Policy (CFA), Aarhus University, Denmark. Lars Geschwind is Professor in Engineering Education Policy and Management, coordinator of the research group HEOS (Higher Education Organization Studies) and Head of the Learning in STEM Division at KTH Royal Institute of Technology, Sweden.